Systematic significance of cypsela morphology in Lessingianthus (Vernonieae, Asteraceae) - Angulo, María Betiana (2015)
Fil: Angulo, María Betiana. Universidad Nacional del Nordeste. Facultad de Ciencias Agrarias; Argentina.